2006
DOI: 10.1080/08880010500506370
|View full text |Cite
|
Sign up to set email alerts
|

MONOTHERAPY WITH PIPERACILLIN/TAZOBACTAM VERSUS CEFEPIME AS EMPIRICAL THERAPY FOR FEBRILE NEUTROPENIA IN PEDIATRIC CANCER PATIENTS: A Randomized Comparison

Abstract: The purpose of this study was to compare the efficacy, safety, and cost of piperacillin/tazobactam with cefepime monotherapy in children with febrile neutropenia. A prospective randomized study in children and adolescent with cancer was conducted. Patients were randomly assigned to receive either 80 mg/kg piperacillin/10 mg/kg tazobactam every 6 h (maximum 4.5 g/dose) or cefepime 50 mg/kg every 8 h (maximum 2 g/dose). Treatment modification was defined as all the changes in the empirical antimicrobials after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
32
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 25 publications
10
32
1
3
Order By: Relevance
“…Paul et al (2010) have shown that ceftazidime, cefepime, PIP/TAZ, and carbapenems were effective as monotherapy in their meta-analysis. The results were in agreement with recent studies including pediatric cancer patients, reporting that cefozopran, cefepime, meropenem,imipenem, sulperazon and piperacillin-tazobactam were effective and safe for empiric treatment of febrile neutropenic episodes (Agaoglu et al, 2001;Corapcioglu et al, 2006;Erbey et al, 2009;Uygun et al, 2009;Vural et al, 2010;Demir et al, 2011;Erbey et al, 2010;Ichikawa et al, 2011;Karaman et al, 2012). Vural et al (2010) compared PIP/ TAZ versus imipenem in pediatric febrile neutropenia and reported that both antibiotics can be used safely as monotherapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Paul et al (2010) have shown that ceftazidime, cefepime, PIP/TAZ, and carbapenems were effective as monotherapy in their meta-analysis. The results were in agreement with recent studies including pediatric cancer patients, reporting that cefozopran, cefepime, meropenem,imipenem, sulperazon and piperacillin-tazobactam were effective and safe for empiric treatment of febrile neutropenic episodes (Agaoglu et al, 2001;Corapcioglu et al, 2006;Erbey et al, 2009;Uygun et al, 2009;Vural et al, 2010;Demir et al, 2011;Erbey et al, 2010;Ichikawa et al, 2011;Karaman et al, 2012). Vural et al (2010) compared PIP/ TAZ versus imipenem in pediatric febrile neutropenia and reported that both antibiotics can be used safely as monotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…Gulay Sezgin*, Can Acipayam, Ayse Ozkan, Ibrahim Bayram, Atila Tanyeli include anti-pseudomonal cephalosporins, carbapenems, ureidopenicillins, and cephalosporins combined with beta lactamase inhibitors (Agaoglu et al, 2001;Corapcioglu et al, 2006;Erbey et al, 2009;Uygun et al, 2009;Erbey et al, 2010;Vural et al, 2010;Demir et al, 2011;Ichikawa et al, 2011;Karaman et al, 2012).…”
Section: Meropenem Versus Piperacillin-tazobactam As Empiric Therapy mentioning
confidence: 99%
“…The therapeutic success rate without modifications in these studies was similar to ours (60-70%) in the CFP arm. However, different from those studies, we analyzed only patients with leukemia and lymphoma (high-risk), the other studies included almost 30% of patients with solid tumors, known to be at a lower risk and to have a higher success rate [6,15,16,23,29,30] .…”
Section: -----------------------------------------------mentioning
confidence: 99%
“…Etkenlerin üretilmesi güçtür ve yaklafl›k üçte biri gösterilebilmektedir. S›kl›kla saptanan etkenler KNS, S.aureus, P.aeruginosa, E.coli ve K.pneumoniae'dir (12)(13)(14)(15)(16)(17) …”
Section: Tart›flmaunclassified